Ensino e aprendizagem da escrita em sala de aula: práticas interativas e dialógicas na produção de artigo de opinião e notícia - Ferreira, Taith Braz Teles (2020)
Resumo em língua estrangeira: The teaching of text production in Portuguese, as highlighted by Antunes (2003), Passarelli (2012) and Geraldi (2013,2015), in many contexts of basic education teaching, is still based on abstract, meaningless proposals and disconnected from students' social practices skills. Contrary to this conception, we defend the idea that, for the teaching of textual production, we need to understand that texts have authorship, interlocutors are provided, have a definite communicative purpose and are part of some social situation. In view of this, two didactic sequences were elaborated aiming to create interactive and dialogical situations in the classroom in order to subsidize the students' text production so that we can analyze how such practice can contribute to the writing learning of the Portuguese language. Therefore, we develop language actions whose conception refers to the view of writing as a dialogical, interactional and social activity. To follow this path, we base ourselves on the theoretical postulates of Bakhtin and Volochínov (2014) with regard to the dialogical and ideological nature of language; in Bakhtin (2018) and Marcuschi (2008), for language teaching practices via discursive genres; and in Antunes (2003, 2009, 2010, 2017), Geraldi (1996, 2011, 2013, 2015), Koch and Elias (2018) and Passarelli (2012), theories about working with the text in the classroom from the sociointeractionist conception. The study also uses the postulations of Dolz, Noverraz and Schneuwly (2010) in relation to working with discourse genres via didactic sequences; Koch (2012), Fiorin (2018) and Casseb-Galvão and Duarte (2018) in relation to the argumentative construction of texts. The qualitative approach and action research are the methodological guidelines of this research, because, according to Bortoni-Ricardo (2008), action research seeks to understand and interpret social phenomena inserted in a context. The study was carried out in a public school in the city of Goiânia (GO), in two classes of thirty high school students at night. As a corpus, we used the students' textual productions and the notes in the field diary. For the analysis of textual productions, we based ourselves on the proposal of Antunes (2010), bringing to this study the understanding that writing is a dialogical and cooperative activity. We hope to contribute to the writing learning process of the Portuguese language, providing students with direct experience with language as a phenomenon in use. To this end, we created, as educational products, two didactic sequences, focusing on working with opinion and news articles from the discourse genres and a website in the form of an online mini-newspaper entitled Gazeta do Estudante, where students were able to publish their textual productions during the application of didactic sequences. By creating the website we aimed to work the language as a social practice as well as to value students’ writing.